Cash Waqf in Poverty Reduction in India: Lessons from Selected Countries - Owais, Mohd; Qutaiba, Mohammad (Talaa : Journal of Islamic Finance, 2023)
Cash Waqf revived in Muslim countries allows them to develop this system of charity further. However, Waqf has abundant financial and infrastructure resources in India, which can significantly reduce poverty, particularly among Muslims. Poverty is more prevalent among Muslims in India than in any other community. This library-based research aims to examine how faith-based endowments can reduce poverty in India through cash waqf. This study applies the content analysis of the existing cash waqf models, which examines current Waqf practices for their relationship to India's socio-economic situation. It helps to understand the adoption of cash waqf in India. The paper implemented the waqf shares scheme based on existing literature. Several important reasons make this scheme appropriate for India. First, raising funds from the public is a relatively straightforward process in India by using traditional ways of collecting money, such as cash collections or mobile payment systems that are widely used for raising money. Several poor Indians could benefit from the funds generated by creating employment opportunities and gaining financial, social, and educational empowerment.